2021
DOI: 10.3390/ma14071783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cutting-Tool Coating on the Surface Roughness and Hole Dimensional Tolerances during Drilling of Al6061-T651 Alloy

Abstract: Aluminum alloys are soft and have low melting temperatures; therefore, machining them often results in cut material fusing to the cutting tool due to heat and friction, and thus lowering the hole quality. A good practice is to use coated cutting tools to overcome such issues and maintain good hole quality. Therefore, the current study investigates the effect of cutting parameters (spindle speed and feed rate) and three types of cutting-tool coating (TiN/TiAlN, TiAlN, and TiN) on the surface finish, form, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…Similarly, in the case of AA6061, the lowest circularity error was 0.0237 mm at the n of 3025 rpm and f of 0.08 mm/rev. A comparison between the results reported in this study and previous studies [24,25] on the same alloys and drill diameter, with the annotation that different feed rates, spindle speeds, tool geometry, and coatings were used, showed that hole circularity in AA2024 and AA6061 alloys was not critically influenced by the cutting tool coating or the level of cutting parameters. This conclusion is further supported by the ANOVA results shown in Table 3, which showed that both cutting parameters did not significantly affect hole circularity and displayed a non-linear trend at the circularity error, which could be confirmed by p-values of more than 0.05.…”
Section: Analysis Of Hole Size Analysis and Circularity Errorsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, in the case of AA6061, the lowest circularity error was 0.0237 mm at the n of 3025 rpm and f of 0.08 mm/rev. A comparison between the results reported in this study and previous studies [24,25] on the same alloys and drill diameter, with the annotation that different feed rates, spindle speeds, tool geometry, and coatings were used, showed that hole circularity in AA2024 and AA6061 alloys was not critically influenced by the cutting tool coating or the level of cutting parameters. This conclusion is further supported by the ANOVA results shown in Table 3, which showed that both cutting parameters did not significantly affect hole circularity and displayed a non-linear trend at the circularity error, which could be confirmed by p-values of more than 0.05.…”
Section: Analysis Of Hole Size Analysis and Circularity Errorsupporting
confidence: 56%
“…The influence of n was found to be 9.71%, while the two-way interaction of spindle speed and alloy type significantly impacted hole size with a contribution of 24.81%. Similarly, hole size deviation in the AA6061 alloy reported in this study was significantly lower than that reported in a recent study [24]. The only difference in the tools used in both studies was that the previous study used coated tools (TiN, TiAlN, and TiN/TiAlN), while the current study used uncoated tools.…”
Section: Analysis Of Hole Size Analysis and Circularity Errorsupporting
confidence: 43%
“…Poor hole quality can lead to part rejections in quality control. Hence, a higher degree of research is required to enhance the holes' quality and minimise the incidence associated with the drilling operation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The drill bits used were an uncoated and (TiN, TiCN, TiAlN, and TiSiN) coated carbide twist drill with a 6 mm diameter [26]. The selection of coatings was based on their excellent hardness and high thermal and oxidation resistance that contributes to the improvement of holes [27,28]. Some of the properties of drill bits are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%